2024
DOI: 10.1021/acs.jpca.3c06456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the OH-Stretching Bands of the Methanol Dimer

Emil Vogt,
Casper Vindahl Jensen,
Henrik G. Kjaergaard

Abstract: We present a conceptually simple model for understanding the significant spectral changes that occur with the temperature in the infrared spectra of hydrogen-bound complexes. We have measured room-temperature spectra of the methanol dimer and two deuterated isotopologues in the OH(D)-stretching region. We correctly predict spectral changes observed in the gas phase for the bound OH stretch in the methanol dimer from jet-cooled to room temperature and corroborate this with experimental and theoretical results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…The peak location of the cold clusters are supported by other studies including cavity ringdown and predissociative size selected molecular beam depletion experiments. ,,, These three maxima all appear at the onset of the fitted band profiles in our room temperature spectra, which we assign as the MeOH tetramer, trimer, and dimer. In general, it has been observed that cold OH b -stretching absorption bands are positioned at the low energy onset of the thermal band counterparts in bimolecular hydrogen bound complexes. ,,, For (MeOH) 2 , spectra at both cold and warm conditions are available with limited interfering absorbance from other clusters, ,, and ab initio simulated band profiles at various temperatures have recently been presented . In Figure , we show a comparison between our fitted (MeOH) 2 band profile and an experimental and simulated band profile at room temperature from ref .…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The peak location of the cold clusters are supported by other studies including cavity ringdown and predissociative size selected molecular beam depletion experiments. ,,, These three maxima all appear at the onset of the fitted band profiles in our room temperature spectra, which we assign as the MeOH tetramer, trimer, and dimer. In general, it has been observed that cold OH b -stretching absorption bands are positioned at the low energy onset of the thermal band counterparts in bimolecular hydrogen bound complexes. ,,, For (MeOH) 2 , spectra at both cold and warm conditions are available with limited interfering absorbance from other clusters, ,, and ab initio simulated band profiles at various temperatures have recently been presented . In Figure , we show a comparison between our fitted (MeOH) 2 band profile and an experimental and simulated band profile at room temperature from ref .…”
Section: Resultsmentioning
confidence: 93%
“…The change in absorbance between the high pressure spectrum and the low pressure reference spectrum becomes apparent when magnified by a factor of 10, and clearly reveals a wide cluster absorption band with three maxima located at 3390, 3526, and 3598 cm –1 , respectively. The spectrum resembles previous spectra recorded at room temperature and consists of absorbance contributions from OH b -stretching transitions in the MeOH dimer, trimer and tetramer. , We deconvolute the band by fitting three band profiles, one for each order of cluster, with each cluster band profile consisting of the sum of two Voight profiles slightly shifted from each other to allow for asymmetric band-shapes …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations